Efficient H2O2 Production via H2O Oxidation on an Anode Modified with Sb‐Containing Mixed Metal Oxides. Issue 11 (3rd June 2020) - Miyase, Yuta; Miseki, Yugo; Gunji, Takahiro; Sayama, Kazuhiro
Abstract: The effect of the surface modification of a fluorine‐doped tin oxide (FTO) electrode with an Sb‐containing mixed metal oxide on the oxidative production of H2 O2 from H2 O was investigated. The initial faradaic efficiency for H2 O2 production (FE(H2 O2 )) reached 98 % when CuSb2 O x /FTO was used as the anode, as a consequence of the suppression of O2 generation via four‐electron oxidation of H2 O. InSbO x modification of FTO resulted in a suppression of the oxidative decomposition of H2 O2 to O2 . The double‐layer composite electrode InSbO x /CuSb2 O x /FTO indicated the advantageous traits of both Sb‐containing mixed metal oxides, and this composite electrode showed superior FE(H2 O2 ), current‐potential dependence, and stability to other electrodes such as CuSb2 O x /FTO, InSbO x /FTO, and Al2 O3 /BiVO4 /FTO. Abstract : The key ingredient : In this work, a new metal‐oxide based electrocatalyst was investigated for H2 O2 production from H2 O. Efficient and stable H2 O2 production could be achieved using an InSbO x /CuSb2 O x /FTO anode in an aqueous solution containing KHCO3 .